2018
DOI: 10.1063/1.5023503
|View full text |Cite
|
Sign up to set email alerts
|

MRI analysis to map interstitial flow in the brain tumor microenvironment

Abstract: Glioblastoma (GBM), a highly aggressive form of brain tumor, is a disease marked by extensive invasion into the surrounding brain. Interstitial fluid flow (IFF), or the movement of fluid within the spaces between cells, has been linked to increased invasion of GBM cells. Better characterization of IFF could elucidate underlying mechanisms driving this invasion in vivo . Here, we develop a technique to non-invasively measure interstitial flow velocities in the glioma microenvironment of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…The pathological changes in conditions such as glioma or stroke can alter multiple aspects of the ISS, which may include changes in geometry, ECM and its components, the constituents of the ISF, and the transport of substances in the ISS [1,100,101]. In glioma, the uncontrolled growth of tumor cells disrupts the standard architecture of brain tissue.…”
Section: Status Of Iss In Neurological Disordersmentioning
confidence: 99%
“…The pathological changes in conditions such as glioma or stroke can alter multiple aspects of the ISS, which may include changes in geometry, ECM and its components, the constituents of the ISF, and the transport of substances in the ISS [1,100,101]. In glioma, the uncontrolled growth of tumor cells disrupts the standard architecture of brain tissue.…”
Section: Status Of Iss In Neurological Disordersmentioning
confidence: 99%
“…Regarding GBM, paths of brain tumor dissemination correlate with bulk fluid pathways 19 . Additionally, we now know that interstitial fluid flow pathways within GBM in mice are complex and heterogeneous, indicating a need for greater understanding of the impacts on cellular invasion 20 . Only recently we showed that interstitial flow indeed increases invasion of both murine and human glioma cells in vitro through the chemokine receptor-ligand pair CXCR4-CXCL12 6 , 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In the interstitium, a typical L is ~100 μm (approximate distance between microvessels) (Dewhirst and Secomb, 2017). A typical v interstitial is ~1 μm/s (Wiig and Swartz, 2012), although this value can be much lower or higher depending on the region of the tumor (Kingsmore et al, 2018). Finally, a representative value for D is ~10 −7 cm 2 /s (Chary and Jain, 1989) (reported for serum albumin in both normal and neoplastic tissues).…”
Section: Fundamentals Of Mass Transport In the Tumor Interstitiummentioning
confidence: 99%